K-scope: A Java-Based Fortran Source Code Analyzer with Graphical User Interface for Performance Improvement - Terai, Masaaki; Murai, Hitoshi; Minami, Kazuo; Yokokawa, Mitsuo; Tomiyama, Eiji (2012 41st International Conference on Parallel Processing Workshops, 2012)
Given that scientific computer programs are becoming larger and more complicated, high performance application developers routinely examine the program structure of their source code to improve their performance. We have developed K-scope, a source code analysis tool that can be used to improve code performance. K-scope has graphical user interface that visualizes program structures of Fortran 90 and FORTRAN 77 source code and enables static data-flow analysis. To develop the tool, we adopted the filtered abstract syntax tree (filtered-AST) model with Java to visualize the program structure efficiently. Filtered-AST, which extends the AST in the structured programming model by abstract block structuring, is suitable for visualization program structures. Based on this model, K-scope has been developed as an experimental implementation. It constructs filtered-AST objects from both source and intermediate code generated by the front-end of the XcalableMP compiler. We provide illustrations of the graphical user interface and give detailed examples of the tool applied to an actual application code.